Approaches to Protection of Undisclosed Information (Trade Secrets) Background Paper - Schultz, Mark F.. (OECD Publishing, 2014)
This paper takes stock of the available legal protection for trade secrets (undisclosed information) in a broad sample of countries. Drawing on national and international material, the paper develops and presents an indicator of the stringency of protection of trade secrets (the Trade Secrets Protection Index) and provides an assessment of variation in the available protection. The result is a finding that while the sample countries have some similarities, notably with respect to definition and scope of trade secrets, they have many more substantial dissimilarities with respect to implementation of protection for trade secrets. For example, differences are particularly pronounced in evidence gathering and discovery, protection of trade secrets during litigation, technology transfer requirements and the effectiveness of legal systems with respect to enforcement. This diversity is reflected in the wide range of scores in the Trade Secrets Protection Index. Such variation in the stringency of protection for trade secrets may influence firm-level decision-making and may have implications for some aspects of economic performance (in particular, in relation to innovation)
Keywords: Trade